Advocacy Model for Combined Process (Med-Arbitration)-Based Resolution of Industrial Relations Conflicts Between Trade Unions and Businesses - Nurhayati, Siti; Rafianti, Fitri; Wakhyuni, Emi; Hutabarat, Willyam Lorencius (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
In the process of settling labor-management conflicts, trade unions play a crucial role for employees, employers, and trade unions themselves. According to Law Number 2 of 2004 concerning Industrial Relations Dispute Settlement, disputes about labor relations are settled through Bipartite, Tripatrit (labor relations mediation, conciliation, and arbitration), and if non-litigation legal remedies (apart from arbitration) fail, the matter is then brought before the Industrial Relations Court. Due to its proven effectiveness in resolving commercial conflicts, the combined process (med-arb) idea is thought to facilitate dispute resolution in industrial relations problems. Two issues are addressed in this research: the idea of combined process (med-arb) as it applies to the resolution of labor-union disputes with employers and the idea of legal certainty in the process of using combined process (med-arb) to resolve labor-union disputes with employers.